The methylation profile of IL4, IL5, IL10, IFNG and FOXP3 associated with environmental exposures differed between Polish infants with the food allergy and/or atopic dermatitis and without the disease - Gorzkiewicz, Marta; Łoś-Rycharska, Ewa; Gawryjołek, Julia; Gołębiewski, Marcin; Krogulska, Aneta; Grzybowski, Tomasz (Frontiers in Immunology, 2023)
Objectives: Epigenetic dynamics has been indicated to play a role in allergy development. The environmental stimuli have been shown to influence the methylation processes. This study investigated the differences in CpGs methylation rate of immune-attached genes between healthy and allergic infants. The research was aimed at finding evidence for the impact of environmental factors on methylation-based regulation of immunological processes in early childhood.The analysis of methylation level of CpGs in the IL4, IL5, IL10, IFNG and FOXP3 genes was performed using high resolution melt real time PCR technology. DNA was isolated from whole blood of Polish healthy and allergic infants, with food allergy and/or atopic dermatitis, aged under six months.The significantly lower methylation level of FOXP3 among allergic infants compared to haealthy ones was reported. Additional differences in methylation rates were found, when combining with environmental factors. In different studied groups, negative correlations between age and the IL10 and FOXP3 methylation were detected, and positive -in the case of IL4. Among infants with different allergy symptoms, the decrease in methylation level of IFNG, IL10, IL4 and FOXP3 associated with passive smoke exposure was observed. Complications during pregnancy were linked to different pattern of the IFNG, IL5, IL4 and IL10 methylation depending on allergy status. The IFNG and IL5 methylation rates were higher among exclusively breastfed infants with atopic dermatitis compared to the non-breastfed. A decrease in the IFNG methylation was noted among allergic patients fed exclusively with milk formula. In different study groups, a negative correlation between IFNG, IL5 methylation and maternal BMI or IL5 methylation and weight was noted. Some positive correlations between methylation rate of IL10 and child's weight were found. A higher methylation of IL4 was positively correlated with the number of family members with allergy.The FOXP3 methylation in allergic infants was lower than in the healthy ones. The methylation profile of IL4, IL5, IL10, IFNG and FOXP3 associated with environmental exposures differed between the studied groups. The results offer insights into epigenetic regulation of immunological response in early childhood.